2015
DOI: 10.1128/genomea.01113-15
|View full text |Cite
|
Sign up to set email alerts
|

Correction for Sheflo et al., Complete Genome Sequences of Five Brevibacillus laterosporus Bacteriophages

Abstract: The species infected by the five bacteriophages was misidentified as Paenibacillus larvae. The article title should read as given above, and the organism identified as Paenibacillus larvae should be identified as Brevibacillus laterosporus throughout. Page 1: The abstract should read as follows. "Brevibacillus laterosporus is a secondary invader following European foulbrood (EFB) infection of honeybees. We isolated bacteriophages from soil containing bee debris collected near beehives in Utah. We announce five… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…The remaining 21 prophage genomes, when containing genes encoding the TSP were considered to belong to the Myoviridae family. Genome comparison revealed that, while 15 prophages were genetically close to members from the same family, ( Brevibacillus laterosporus phages Jimmer1, Jimmer2 and Abouo; Sheflo et al, 2013 ), the remaining six shared identity (84%–100%, with a coverage between 12% and 94%) with previously described siphoviruses, such as phage Lily.…”
Section: Resultsmentioning
confidence: 89%
“…The remaining 21 prophage genomes, when containing genes encoding the TSP were considered to belong to the Myoviridae family. Genome comparison revealed that, while 15 prophages were genetically close to members from the same family, ( Brevibacillus laterosporus phages Jimmer1, Jimmer2 and Abouo; Sheflo et al, 2013 ), the remaining six shared identity (84%–100%, with a coverage between 12% and 94%) with previously described siphoviruses, such as phage Lily.…”
Section: Resultsmentioning
confidence: 89%